The effects of feeding with shrimp or fish fry on growth and mantle lipid composition of juvenile and adult cuttlefish (Sepia officinalis) - Almansa, Eduardo (2018)
In the present study, cuttlefish (Sepia officinalis) aged 60-day-old (age-group I) and 120-day-old (age-group II) were fed with live shrimp and live fish fry for 60 days, in order to study the diet influence on growth, mantle lipid composition, and astaxanthin content in the skin. The most noteworthy difference was the higher growth observed in shrimp-fed cuttlefish with respect to fishfed cuttlefish in both age groups. Total lipids (TL), lipid classes (LC) and their associated fatty acids (FA) from both diets and mantle of cuttlefish were analysed. The lipid profiles of both diets were clearly different in their LC distribution, with higher levels of Polar Lipids (PL) in shrimp with respect to fish fry. However, both diets did not show outstanding differences in the FA composition of TL except for 20:5n-3 (EPA), which was higher in shrimp than in fish fry. With respect to lipid composition of cuttlefish mantle, the TL content and cholesterol (CHO) percentage increased with age, while phosphatidylinositol (PI) and phosphatidylcholine (PC) percentage decreased. On the other hand, phosphatidylserine (PS), phosphatidylethanolamine (PE) and PC percentages in both cuttlefish age groups were also affected by the different diets, although this difference was higher in agegroup I. The general pattern of fatty acid composition of TL in the mantle of cuttlefish was similar in all groups studied. It is remarkable the low levels of monoene FAs in both age-group cuttlefish mantle, despite of the high level of this FA group in both diets, which suggests that these FAs are not stored in the mantle. An opposite tendency was observed regarding the n-3 HUFA, especially 22:6n-3 (DHA) which remained constant despite the different age or diet. High levels of astaxanthin were found in shrimp with respect to fish, but this was only reflected on skin accumulation in age-group I, showing no differences in age-group II. This suggests differences in the astaxanthin metabolism according to the age. The results suggest that the growth differences observed in shrimp-fed cuttlefish with respect to fish-fed cuttlefish were not reflected in outstanding differences in mantle composition.